Sécurité et détente : Dimensions historiques et problèmes actuels de la politique de sécurité ouest-allemande - Lucas, Hans-Dieter (Études internationales, 1984)
Against the background of the latest vehement discussions in West-Germany on the implementation of the NATO twin-track-decision this article analyses the current concepts of security and détente presented by the main political forces as well as their historical dimensions. The Christian Democrat/Liberal government pursues a pragmatic Atlanticist security policy, which is based largely upon Adenauer's principles such as exclusive definition of West German interests in the framework of the Alliance, rejection of one-sided disarmament and nuclear disengagement. Nevertheless, the government Kohl has adopted the main instruments of the new "Ostpolitik" in order to establish the calculability of West German policy in East and West. Détente is no considered as a political aim in itself. The Social Democrat concept of a security partnership with the East is strongly influenced by the principles and methods underlying the new "Ostpolitik". This concept aims at the creation of a denuclearized zone in Central Europe in order to facilitate a real détente between East and West. An optimistic view or détente appears to be an essential element of the political identity of the SPD. The ideas of the Greens and the "Peace Movement" - unilateral disarmament, creation of a denuclearized zone, renunciation on "first Use" - are variations of the pacifistic concepts already developped in the 1950's. The main reason for the formation of the "Peace Movement" is a change in West German political culture involving above all the younger population.